2006
DOI: 10.1007/s00417-005-0201-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between systemic arterial stiffness and age-related macular degeneration

Abstract: Patients with AMD have increased systemic arterial stiffness compared with age-matched controls. Treatments aimed at preventing or reversing systemic arterial stiffness may also be effective in preventing the onset or slowing the progression of AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
0
17
0
5
Order By: Relevance
“…Type VIII collagen is involved in VSMC migration, differentiation, and morphogenesis and is upregulated after vascular injury, [23][24][25] Collagen type VIII is moreover related to arterial stiffness in an animal model, 26 and polymorphisms in the COL8A1 gene are associated with age-related macular degeneration, a condition known to correlate with measures of arterial stiffness. [27][28][29] Collagen α-1 (IV) is abundantly present in the vascular wall, where it is the main component of basement membranes. 22 Its role in the vasculature is not well defined; however, it is interesting that a genome-wide association study of 4221 individuals found that a polymorphism in COL4A1 was highly significantly associated with PWV 30 and that an experimental study has found that mice with COL4A1 missense mutations display defects in several vascular functions and show low blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Type VIII collagen is involved in VSMC migration, differentiation, and morphogenesis and is upregulated after vascular injury, [23][24][25] Collagen type VIII is moreover related to arterial stiffness in an animal model, 26 and polymorphisms in the COL8A1 gene are associated with age-related macular degeneration, a condition known to correlate with measures of arterial stiffness. [27][28][29] Collagen α-1 (IV) is abundantly present in the vascular wall, where it is the main component of basement membranes. 22 Its role in the vasculature is not well defined; however, it is interesting that a genome-wide association study of 4221 individuals found that a polymorphism in COL4A1 was highly significantly associated with PWV 30 and that an experimental study has found that mice with COL4A1 missense mutations display defects in several vascular functions and show low blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic distensibility and PWV reflect aortic elastic properties which are linked to increased cardiovascular morbidity and mortality in different diseases such as atherosclerosis, hypertension, and diabetes mellitus [11][12][13][14]. Some studies have reported an association between increased AS and diseases like age-related macular degeneration, retinal arterial narrowing and BRVO [15][16][17]. In the present study, we aimed to determine whether AS in different segments of the arterial tree is increased in patients with BRVO.…”
Section: Introductionmentioning
confidence: 94%
“…The results of the current study are the first to show that a proper level of aortic stiffness is related to the development of exudative AMD. The pulse wave velocity (PWV) has also been reported to be a parameter of arterial stiffness 24,25) , and a relationship between AMD and the PWV has been documented 26) . However, the PWV is dependent on the blood pressure at the time of measurement 16) .…”
Section: Discussionmentioning
confidence: 99%